Types of Activity as Determinants of Innovative Potential Development in Personality - O B Mikhailova (Peoples' Friendship University of Russia (RUDN University), 2012)
The most prominent characteristic of the given article is a cultural, historical and theoretical analysis of the main source of all innovations in the society, which is an innovative potential in a personality. The author closely describes the evolution of the terms "innovation" and "potential" in different fields of research. The relation between the innovation activity and the activity of a personality is also considered in the article. It further provides an analysis of the phenomenon of activity in differential psychology, on the basis of which an assumption is made that the innovative potential in a personality is determined by different types of activity.